The Relation between Formulaic Expressions Fluency and Proficiency of Indonesian EFL College Students Using E-book Instructions Via Edmodo - Sukma Indra Dewi, Radeni; Mujiyanto, Januarius; Rukmini , Dwi; Saleh, Mursid (International Journal of Psychosocial Rehabilitation, 2020)
This study targeted to research the students’ strategies in the use of formula expressions in accordance with what is taught in the curriculum through e-book instructions via Edmodo and when taking oral proficiency exam with multi-task. It also aims to investigate if there is a correlation with the utilization of formulaic expressions with fluency and proficiency scores overall. This study was conducted in 190 Indonesian students with different ability levels in Ivet University of Semarang.Content analysis of e-book instructions via Edmodo carried out to find ways to use the formula language by students and determine the target list of the formula language at the frequency of each phrase in the book. Then the video recording content analysis of oral proficiency examination was also carried out to reveal the students’ use of formulaic expressions and the two findings analyzes the content than to draw conclusions.Scores achieved by students in the smoothness and finesse analyzed to connect students with the utilization of formulaic expressions fluency and their overall skills.